PENGEMBANGAN SISTEM PENJADWALAN KULIAH MENGGUNAKAN ALGORITMA STEEPEST ASCENT HILL CLIMBING - Saifullah, Shoffan; Hermawan, Arief (Jurnal Sistem Komputer, 2016)
University of Technology Yogyakarta is a private university in Yogyakarta, it has several purposes, one of them is utilizing the maximum potential of technology to improve the effectiveness and efficiency of learning and dissemination of science and technology. One of the factors that can improve academic services are scheduling courses. Scheduling proses isn’t easy because they have to consider the possibility in scheduling, include subjects, times, lecturers, and lecture halls. Now, subject scheduling is still using Ms. Excel, the process is to input lecturer’s name one by one, to teach to the prescribed schedule and also to check whether the data is conflicting or not, so it takes long time. Therefore, we need a system that is able to perform scheduling more quickly, effectively and optimally. Subject scheduling system can be done by using the optimization system. For the case of optimization can be done using the steepest ascent hill climbing algorithm. Steepest ascent hill climbing algorithm is a search algorithm (heuristic), it is able to solve the problems of optimization with estimates to be produced in accordance with the desired criteria or rules. Subject scheduling process produces a schedule that takes less time compared to a system that is currently running. Although it is able to minimize the level of clashing schedules, its application needs to be re-checked on the level of conflicting schedules.